Fatores prognósticos do carcinoma de células escamosas oral em pacientes jovens e não-jovens: Uma revisão sistemática e meta-análise - Macêdo Filho, Robeci Alves (2018)
Introduction: Oral squamous cell carcinoma (OSCC) ten most prevalent malignant neoplasms in the world, affecting, in majority, men between the fifth and sixth decade of life, which are exposed to the main risk factors such as alcoholism and smoking. However, in the last years it has become evident a significant increase in cases among young individuals, which are generally not exposed to the main risk factors. This has led to the development of researches evaluating the biological behavior and prognostic of OSCC between young and non-young patients. Objective: To compare the prognostic factors of OSCC in young and non-young patients through a systematic review and meta-analysis. Material and Methods: An electronic search was conducted in the databases Pubmed, Scopus, Ovid, Proquest, Cochrane library, Web of Science and Lilacs, and updated on April 2018, without restrictions regarding language or year of publication. Only cohort studies were included and were evaluated for the risk of bias through the Newcastle-Ottawa scale. Analysis of titles/abstracts was performed by two independent and calibrated researchers (Kappa = 0.94). Included studies were evaluated with regard to methodological heterogeneity. Meta-analysis was performed, as included studies were methodologically homogenous. Results: A total of 6,525 articles were reviewed and 10 retrospective cohort studies were selected. All included studies had a low risk of bias. Sample size across studies varied from 45 to 39,570 subjects. Age groups dichotomizing young and non-young patients were mostly based on the age of 45 years-old. With regard to prognostic factors, 80% of studies evaluated smoking and alcoholism as deleterious habits in the age groups, all studies found a predominance of OSCC among men, however, there was an increased number of women among young patients, when compared to non-young individuals. Regarding anatomical location, tongue was the most common anatomical site for both age groups. With regard to clinical staging and histological grading, both groups were diagnosed, mostly (33.3%, n=2), in the early stages (I and II) and were moderately differentiated, respectively. The main prognostic factor evaluated among age groups with OSCC was overall survival, which was reported in 80% of studies. There was an increased overall survival time for non-young patients, however a higher predisposition of relapse was observed among young patients. Regarding meta-analysis, non-young individuals had a 2.24 fold greater chance of smoking than young subjects [OR=2.24; CI= 1.58-3.16; I^2=17%] ; young subjects had a 1.24 fold greater chance of OSCC in the tongue than non- young subjects [OR=1.67; CI=1.25-2.22; I^2 =72%]; non-young subjects had a 2.09 fold greater chance of having well differentiated tumors than young subjects [OR=2.09; CI=1.41-3.09; I^2=0%] ; and non-young subjects had a 1.21 fold greater chance of having been submitted to isolated treatment (one therapy) than young subjects [OR=1.21; CI=1.03-1.42; I^2 =21%]. With regard to overall survival, it was observed that young individuals had a 1.54 fold greater chance of an increased survival when compared to non-young subjects [OR=1.54; CI=1.14- 2.08; I^2 =65%]. Conclusions: Among all prognostic factors evaluated, there were differences in anatomical site and histopathological grading in young patients, however, the overall survival was different between age groups, suggesting that OSCC may present a more aggressive biologic behavior in non-young patients.